122 Long-term impact of community-based participatory women's groups on child and maternal mortality and child disability in rural nepal: follow-up of a cluster randomised trial. (December 2018) - Heys, M; Gram, L; Wade, A; Haworth, E; Osrin, D; Khadka, S; Shrestha, DK; Neupane, R; Adhikari, D; Adhikari, RK; Budhathoki, B; Manandhar, DS; et al.
Abstract : Background: Community-based women's groups practising participatory learning and action (PLA) can reduce maternal and neonatal mortality in low-income countries. However, it is not clear whether these reductions are associated with subsequent increased or decreased rates of disability. We assessed their impact on maternal and child mortality and childhood disability among participants in the earliest trial in Nepal (2001–2003). Methods: Household interviews were conducted with mothers or household heads. Survival data were additionally collected from relatives or neighbours where the index mother and/or child were not contactable. We analysed mortality and disability outcomes at cluster and individual level using pairwise log relative risks and multilevel logistic models respectively. Findings: From 6075 children and 6117 mothers alive at 4 weeks postpartum, we collected survival data on 5990 mothers and 5915 children. Of these, 4419 children (73%) and 4521 (74%) mothers were available for interview an average of 11.5 years later. Accounting only for deaths reported by interview after trial completion, rates of child mortality, maternal mortality and child disability per 1000 participants were 36.6, 3.2 and 62.7 in the intervention arm and 52.3, 4.7 and 85.5 in the control arm. Individual level analysis, including random effects for cluster pairing and adjusted for baseline maternal literacy and socio-economic status, showed lower, statistically non-significant, rates of child mortality (Odds Ratio (OR) 0.70 (95% Confidence Interval (CI) 0.42, 1.16) and disability (OR 0.65 (0.40, 1.07)) in the intervention arm. Interpretation: Reductions in newborn mortality following community level exposure to women's groups practising PLA were not associated with later childhood disability. Furthermore, our data could not exclude additional long-term survival and disability benefits. Our findings highlight the importance of the perinatal period as a critical time to set the path for a healthier childhood.